2015
DOI: 10.1152/ajplung.00090.2015
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of surfactant protein D treatment in 1,3-β-glucan-modulated allergic inflammation

Abstract: Surfactant protein D (SP-D) is a pulmonary collectin important in lung immunity. SP-D-deficient mice (Sftpd(-/-)) are reported to be susceptible to ovalbumin (OVA)- and fungal allergen-induced pulmonary inflammation, while treatment with exogenous SP-D has therapeutic effects in such disease models. β-Glucans are a diverse group of polysaccharides previously suggested to serve as fungal ligands for SP-D. We set out to investigate if SP-D could interact with 1,3-β-glucan and attenuate allergic pulmonary inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…More recently, the role of β-glucans has been directly examined. One study found that exposure to curdlan plus OVA allergen resulted in a modest increase in lung inflammation and neutrophilia in mice [73]. Recently, our group directly compared exposure to fungal spores combined with house dust mite (HDM) allergen and curdlan plus HDM in a mouse model of asthma [12••].…”
Section: Mechanistic Underpinnings Of Health Impact Of Fungal Exposurmentioning
confidence: 99%
“…More recently, the role of β-glucans has been directly examined. One study found that exposure to curdlan plus OVA allergen resulted in a modest increase in lung inflammation and neutrophilia in mice [73]. Recently, our group directly compared exposure to fungal spores combined with house dust mite (HDM) allergen and curdlan plus HDM in a mouse model of asthma [12••].…”
Section: Mechanistic Underpinnings Of Health Impact Of Fungal Exposurmentioning
confidence: 99%
“…Although the model is different to our allergic model, it partly explains decreased IL-5 production and airway eosinophilia in SP-D deficiency. However, a previous study showed that the number of eosinophilia and the production of Th2 cytokines increased in SP-D-deficient mice compared with WT mice after OVA challenge (Schaub et al 2004), while another study showed no difference in eosinophilia between SP-D-deficient and WT mice (Fakih et al 2015). The different protocols of OVA sensitization/challenge may be associated with the different results among these studies.…”
Section: Discussionmentioning
confidence: 92%
“…), while another study showed no difference in eosinophilia between SP‐D‐deficient and WT mice (Fakih et al. ). The different protocols of OVA sensitization/challenge may be associated with the different results among these studies.…”
Section: Discussionmentioning
confidence: 96%
“…This could indicate that OVA-sensitization and challenge that induce inflammation also reduces variation in microbiota composition. It is worth noting that there were only mild allergic differences between OVA-sensitized and challenged Sftpd+/+ and S ftpd−/-, [21] making it possible to separate the effects of SP-D and allergy on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%